The Representation of Basuki Tjahaja Purnama (BTP) as a Social Actor in the Collection of Hoax News Headlines on www.turnbackhoax.id - Zakie Asidiky; R.Vindy Melliany Puspa (Makassar State University, 2020)
This study aims to describe the representation of Basuki Tjahaja Purnama (BTP) as a social actor and to reveal the ideological stance of the media in collection of hoax news headlines. The approach used in this study is Fairclough’s three-dimensional model of critical discourse analysis (1995, 2013) with a textual metafunction theory as its analytical tool proposed by Halliday and Mattiessen (2014). The data of this study are 17 hoax news headlines that have been verified by their lies on the website www.turnbackhoax.id. The results of this study are (i) the theme and rheme used in the hoax news headlines can help organize messages and play an important role in the headlines from the perspective of the reader, (ii) BTP was explicitly represented as a social actor in some negative ways in those hoax news headlines such as he is supported by those who are not Pro-Islam, fails to eradicate prostitution, powerful person, not brave and involved in law case, (iii) the media’s ideological stance intentionally contradicted to other national media in publishing the hoax news headlines related to BTP and tended to highlight the news without the clear sources and exaggerate the headlines. Furthermore, the result of this study would be a helpful material source for those who would like to prepare the critical literacy materials, specifically, about how to identify the features of hoax news headlines